1984
DOI: 10.1002/art.1780271106
|View full text |Cite
|
Sign up to set email alerts
|

Sjöugren's syndrome influence of multiple hla‐d region alloantigens on clinical and serologic expression

Abstract: The relationships of HLA-DR and the newer DS (second D locus) B cell alloantigens (MB and MT) to the clinical and serologic expression of primary and secondary forms of Sjogren's syndrome (SS) were examined in 102 patients (86 whites and 16 blacks). Although HLA-DR3 was significantly increased in whites (25 of 50, 50%) and blacks (4 of 5, 80%) with primary SS compared with race-matched normal controls, it was not appreciably elevated in those with systemic lupus erythematosus (SLEMS, rheumatoid arthritis (RAb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0

Year Published

1985
1985
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(25 citation statements)
references
References 33 publications
4
21
0
Order By: Relevance
“…In our Japanese patients, the strongest MHC determinant for anti-La was HLA-DR3 and DR2 have been reported to correlate with anti-Ro in white patients (12,14). In our Japanese patients with anti-Ro, a relatively weak correlation with B7 was found.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…In our Japanese patients, the strongest MHC determinant for anti-La was HLA-DR3 and DR2 have been reported to correlate with anti-Ro in white patients (12,14). In our Japanese patients with anti-Ro, a relatively weak correlation with B7 was found.…”
Section: Discussionsupporting
confidence: 44%
“…Our study has shown that autoantibody expressions are related to the different genetic influences coded by HLA antigens (10)(11)(12)(13)(14)(15). The prevalence of autoantibodies t o S m , nRNP, Ro, and La in our Japanese subjects is not very different from that in series of white subjects (data not shown).…”
mentioning
confidence: 91%
“…Earlier reports have shown that in SS, autoimmune reactions to La or Ro antigen are associated with the HLA-DR3 antigen in North European whites (32,33). Furthermore, patients with primary SS who have high antibody titers to Ro and/or La antigen also tend to have leukopenia and hypergammaglobulinemia and are positive for rheumatoid factor more often than other patients with primary SS (2,32,33). In our study, there were no statistically significant differences in the latter clinical parameters, but this may be due partly to the small size of the subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…HLA-A, B, and C antigens were determined by a standard complement-dependent microcytotoxicity method (8). B cell typing for HLA-DR and MT (DQw1, DRw52, and DRw53) specificities was performed using a nylon-wool column method (9) and typing sera standardized with those from the 8th International Histocompatibility Workshop. We could not, however, determine the HLA-DRw6 specificity because of the scarcity of good standard sera for DRw6.…”
Section: Methodsmentioning
confidence: 99%